1999
DOI: 10.1359/jbmr.1999.14.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Fracture in Patients Receiving Solid Organ Transplants

Abstract: The success of organ transplantation is related to advances in immunosuppressive therapy. These medications are associated with medical complications including bone damage. The objective of this study was to estimate and compare age, gender-specific fracture incidence between transplant recipients, and a large sample representative of the civilian noninstitutionalized United States population using the 1994 National Health Interview Survey (NHIS). This was a cohort study set in tertiary care centers. Five hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
2
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(138 citation statements)
references
References 22 publications
10
121
2
2
Order By: Relevance
“…Further, the data highlight that temporal changes in BMD measured at the hip and spine are not associated with detected alterations in stiffness and failure strength at the appendicular sites, which are particularly prone to fracture in renal transplant recipients (6,(8)(9)(10). Additionally, baseline values of failure strength were only weakly correlated with hip BMD while showing no correlation with spine BMD.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Further, the data highlight that temporal changes in BMD measured at the hip and spine are not associated with detected alterations in stiffness and failure strength at the appendicular sites, which are particularly prone to fracture in renal transplant recipients (6,(8)(9)(10). Additionally, baseline values of failure strength were only weakly correlated with hip BMD while showing no correlation with spine BMD.…”
Section: Discussionmentioning
confidence: 80%
“…The risk of fracture among renal transplant recipients increases even further in the months following surgery (7). Interestingly, post-transplantation bone fractures are more frequently located in the appendicular than axial skeleton (8)(9)(10). Dual-energy x-ray absorptiometry (DXA) does not allow distinction between the effect of renal osteodystrophy on cortical and trabecular bone and provides poor fracture discrimination in patients with renal failure (8,11).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Similarly, 27 (16%) patients had either vertebral deformities or a history of a low trauma fracture after transplantation. Ramsey-Goldman et al (10) found that the most common site of fracture was the foot, and this occurred similarly in both premenopausal and postmenopausal women after transplantation.…”
Section: Is There An Increased Fracture Risk After a Kidney Transplant?mentioning
confidence: 98%
“…With regard to fractures, a high incidence of them (between 20% and 40% in most studies) has been documented. In heart and liver transplant recipients, the incidence of new fractures parallels the timing of the most rapid bone loss, with most fractures occurring within the first year after transplantation (Eastell R, 1991;Henderson et al, 1995;Ramsey-Goldman et al, 1999). Fractures usually affect the spine and ribs in liver, cardiac, or lung recipients, whereas long bones are more easily fractured in renal transplant recipients.…”
Section: Bone Loss and Fractures After Transplantationmentioning
confidence: 99%